Project management : the managerial process - Larson, Erik W., 1952-; Gray, Clifford F.; Gray, Clifford F. (New York : McGraw-Hill Irwin, 2011)
This textbook presents a balanced treatment of both the technical and behavioural issues in project management as well as covering a broad range of industries to which project management principles can be applied.
Gray's name appears first on the earlier editions.
Includes index.
Keywords: Project management; Time management; Risk management